Efeito das condições extremas de temperatura e pressão nas propriedades estruturais e vibracionais dos dipeptídeos glicil-L-fenilalanina e glicil-L-ácido glutâmico - Silva, José Avelar Sousa da (2024)
In this study, the structural and vibrational analysis of the dipeptides glycyl-Lphenylalanine (111423) and glycyl-L-hydrated glutamic acid ( 71225 ) was carried out. Glycyl-L-phenylalanine is a hydrophilic dipeptide formed by joining the dipeptides glycine and phenylalanine and is used in the synthesis of co-crystals and metalorganic frameworks (MOFs), while glycyl-L-glutamic acid is a neurotransmitter dipeptide with the potential to prevent certain degenerative diseases, such as Alzheimer's disease. As a first step, the dipeptides were crystallized and their structures determined using X-ray diffraction. In addition to this technique, first-principles calculations using density functional theory (DFT), thermal analysis (differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA)), infrared spectroscopy and Raman spectroscopy under extreme conditions of temperature and pressure were also used. With regard to glycyl-Lphenylalanine, DFT calculations were used to obtain the lowest energy molecular conformation by varying the dihedral angle ω (C1C2N2C3) in an aqueous medium. Vibrational spectra and the theoretical assignment of the normal modes of vibration of the dipeptides were also obtained, and good agreement was found with the experimental data. Raman spectroscopy experiments at high pressures were carried out on the dipeptide glycyl-L-phenylalanine up to pressures of 7.1 GPa, using a diamond end pressure cell. From this study, a phase transition was observed around 1.0 GPa, accompanied by conformational changes according to the analysis of the behavior of various internal modes. Varying the temperature from 300 to 10 K and from 300 to 393 K, a structural phase transition was observed between 100 and 80 K. A non-linear behavior of some wave numbers of high-energy modes was also noted, possibly due to the fact that certain C-H units are coupled with modes involved in hydrogen bonds. With regard to hydrated glycyl- L-glutamic acid, its structure was solved using the single-crystal X-ray diffraction technique, and its crystal structure, space group, atomic positions and lattice parameters were obtained which have not yet been catalogued in the literature. A detailed analysis of the vibrational modes was carried out using first-principles calculations and potential energy distribution (PED). When subjected to temperatures ranging from 300 to 403 K, a non-linear behaviour was observed in the wave number of several bands, pointing to an anharmonicity preceding the amorphization of the sample. The amorphization process itself involved the exit of water molecules above 400 K, indicating that the water present in the structure plays a major role in the stability of the crystal at room temperature. A comparison of this last result with recent studies on other dipeptides is also provided.